A bonding study of cyclopentene (c-C5H8) adsorption on Ni(1 1 1) surface - German, Estefania (2008)
The adsorption of cyclopentene (c-C5H8) on Ni(1 1 1) was studied using DFT and semiempirical calculations. Preferred site and geometry calculations were carried out considering a Ni(1 1 1) surface and a unit cell of 64-atoms. The tetrahedral threefold hollow position was identified as the most favorable site, with a surface-molecule minimum distance of 1.83 Å. A bending structure is adopted when the molecule is adsorbed where the carbon atoms of the double bond are closer to the surface forming an angle of 160° among non-equivalents carbon atoms. The metal surface was represented by a two-dimensional slab with an overlayer of c-C5H8/Ni of 1/9 ratio. We also computed the density of states (DOS) and the crystal orbital overlap populations (COOP) corresponding to Csingle bondC, Csingle bondNi, Csingle bondH, and Nisingle bondNi bonds. We found that both Nisingle bondNi bonds interacting with the ring, and the C{double bond, long}C bond are weakened after adsorption, this last bond is linked significantly to the surface. The hydrogen atoms belonging to the saturated carbon atoms also participate in the adsorbate-surface bonding. The main interactions include the 4s, 3pz and 5 dz2 bands of nickel and 2pz bands of the carbon atoms of the double bond. © 2008 Elsevier B.V. All rights reserved.